Caracterização de espécies de Leishmania isoladas de Flebotomíneos sp. de três ecótopos da Serra dos Carajás, Pará, Brasil - DIAS JUNIOR, Manoel Guacelis de Sena (Universidade Federal do Pará, 2013)
The American cutaneous leishmaniasis (LTA) is an infectious disease, with a high frequency of zoonosis, endemic in the Amazon region, transmitted by sand flies of generous Psychodopygus and Lutzomyia. Serra dos Carajás, located in southeastern Pará, is widely exploited by extractive companies and as a result, the LTA would be transformed into a major health problem to workers because of the practice of deforestation and construction of roads for drainage of the ore. The purpose of this study is to evaluate the natural infection in the sand fly by Leishmania in the Serra dos Carajás region through the PCR. Catches of sandflies were held in three different areas, Parque Zoobotânico de Quarentena, APA do Gelado and Tapirapé-Aquirí, with CDC-type of light traps and Shannon, during the night from the evening twilight. The sand flies captured were identified according to Young & Duncan, 1994, and frozen in N2. 5.947 sandflies were frozen, being 3.495 females and among these 550 specimens were tested. The extraction of DNA was performed using SDS and KOAc and it was precipitated with ethanol 96%. Subsequently, the PCR was performed by amplifying the mini-exon gene with the primers S1629 (5' GGGAATTCAATAWAGTACAGAAACTG 3') and S1630 (5' GGGAAGCTTCTGTACTWTATTGGTA 3'). The DNA of Leishmania was detected in 36 (6,5%) sand flies, 34 of subgenus Viannia detected in 30 Psychodopygus wellcomei/ complexus, three Lutzomyia whitmani and a Lutzomyia shawi. Two infections by Leishmania amazonensis was detected in Psychodopygus wellcomei/ complexus. Tapirapé - Aquirí, APA do Gelado and Parque Zoobotânico de Quarentena showed high rates of natural infection in sand flies 6.54%, 5.96% and 7.92% respectively. Ps. wellcomei/complexus still presents as Leishmania vector that cause LTA. Studies on the power of vector species Lu. whitmani and Lu. shawi naturally infected by Leishmania in the Serra dos Carajás should be intensified, if these species may be acting in the cycle of transmission of LTA in Serra dos Carajás. Studies that best explain the variation of the prevalence of different sandflies species and knowledge of the rate of infections should be also intensified in Serra dos Carajás.